Identifying poly(ADP-ribose)-binding proteins with photoaffinity-based proteomics - Dasovich, Morgan (J Am Chem Soc, 2021)
Post-translational modification of proteins with poly(ADP-ribose) (PAR) is an important component of the DNA damage response. Four PAR synthesis inhibitors have recently been approved for the treatment of breast, ovarian, and prostate cancers. Despite its clinical significance, a molecular understanding of PAR function, including its binding partners, remains incomplete. In this work, we synthesize a PAR photoaffinity probe that captures and isolates endogenous PAR binders. Our method identified dozens of known PAR-binding proteins and hundreds of novel candidates involved in DNA repair, RNA processing and metabolism. PAR binding by eight candidates was confirmed using pull-down and/or electrophoretic mobility shift assays. Using PAR probes of defined lengths, we detected proteins that preferentially bind to 40-mer versus 8-mer PAR, indicating that polymer length may regulate the outcome and timing of PAR signaling pathways. This investigation produces the first census of PAR-binding proteins, provides a proteomics analysis of length-selective PAR binding, and associates PAR binding with RNA metabolism and the formation of biomolecular condensates.